Pembentukan Kelompok Tani Berbasis Singkong Sebagai Upaya Ketahanan Pangan dan Ekonomi Keluarga - Elda Nazriati; Sri Wahyuni; Herisiswanto Herisiswanto; Rofika Rofika; Zulharman Zulharman; Rita Endriani (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2021)
Cassava is one of the foodstuffs that have an important role in supporting food security in a region, but not many people are interested in focusing on developing cassava. Health responsibility in the implementation of food security is embodied in the standard reference and technical health requirements throughout the food management process, the principles of Sanitation Hygiene. Sialang Sakti is one of the sub-districts in Tenayan Raya Subdistrict. It is one of the potential cassava-producing villages to be developed. The purpose of the service activities includes ordering farmer groups that focus on cassava as an effort to food security and the family economy. Activities carried out include advocacy to related parties, Focus Group Discussions (FGD), ordering farmer groups, training, and other activities to support the management and use of cassava as a source of the family's economy. The result of this activity is the formation of farmer groups that focus on the community, increasing knowledge and skills of cassava cultivation, and the existence of appropriate technology products, and partnership with related parties.